Optimalisasi Peran Guru Sebagai Agen Perubahan dalam Pendidikan dan Masyarakat di Era Digital - Mualimin Mualimin; M. Abdullah Hafidz; Dini Zahwa Kamila; Kholifatur Rofiah (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study explores the strategic role of teachers in education and society and the challenges they face in integrating technology in the Industrial Revolution 4.0 era. Using a qualitative approach based on literature studies, this study analyzed four relevant articles. The findings show that teachers have a multifaceted role, including as educators, mentors, motivators, and agents of social change. Teachers are expected to be able to adapt to technological developments to create relevant learning for generation Z, such as through the implementation of the flipped classroom method and project-based learning. However, limited infrastructure and technology training are major challenges. This study emphasizes the importance of continuous training and policy support to support teacher professionalism in meeting the demands of modern education. This study also identifies the need for further research to address gaps in technology training, especially in areas with limited access..